Being a co-worker or a manager of a colleague returning to work after stroke: A challenge facilitated by cooperation and flexibility. (2nd April 2020) - Öst Nilsson, Annika; Eriksson, Gunilla; Asaba, Eric; Johansson, Ulla; Hellman, Therese
Abstract: Background: The process of return to work is complex. Knowledge is scarce regarding the experiences from co-workers and employers about this process. Aim: To explore and describe how co-workers and managers experience the return to work process involving a colleague with stroke who is participating in a person-centred rehabilitation programme focusing on return to work including a work trial. Material and methods: Seven co-workers and four managers were interviewed during the work trial of a colleague with stroke. Results: Being a co-worker or manager was related to various challenging experiences; the emotional challenge of being a supportive co-worker or manager, the challenging experience of having too much responsibility, and the challenge of being supportive despite a lack of knowledge. Conclusions: The participants placed value on having support from the coordinator for handling different challenges, but despite this they experienced difficulties in being a valuable support. The limited time of work trial and occasional lack of support from the employer were aggravating aspects. Significance: This study highlights the importance of establishing a commitment between the employer and all involved actors in the initial phase in order to create the best possibilities for a fruitful return to work process, including work trial.